Valoración económica del servicio ambiental de secuestro de CO2 en un bosque de terraza baja de la comunidad nativa Nuevo Horizonte, distrito del Napo, Loreto. 2021 - Mori Pereira, Liceth Melita (2022)
The economic value of the CO2 sequestration sequestration service was ompared in a low-terrace forest in the Napo district, Loreto, Peru. The data from the forest census of the commercial species of the low-terrace forest of the Nuevo Horizonte native community were evaluated. The results show that the lumber economic value is USD 305 595,17. In addition, V. calophylla (USD 41 006,33), P. nitida (USD 33 575,89), E. grandifolia (USD 28 579,93) and H. excelsum (USD 18 306,34) all together contain the highest economic value of lumber in the study area. The economic value of CO2 sequestration reports USD 1 374 381,11. In addition, P. nitida (USD 232 402,87), E. grandifolia (USD 203 474,26), V. calophylla (USD 122 002,09) and T. oblonga (USD 78 180,22) are the species with higher economic values; while G. glabra (USD 2 136,64), P. peruviana (USD 2 097,55) and A. parvifolium (USD 2 059,39) show lower values. When comparing the net profit from the sale of logs with the economic value of the sequestration of CO2 in the evaluated forest, a difference in favor of the CO2 sequestration service of USD 793 989.44 is observed.